The Exploration students` attitude on Artificial Intelligence in the World of Educations: A Systematic Literature Review - Saharudin Saharudin; Ahmad Syauqi Harsyah; Mukhlas Abrar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This systematic literature review provided several journal articles that contain about students` Attitude on artificial intelligence . This article used three databases, namely ERIC, Google Scholar and Taylor & Francis. A total of 25.093 articles were appeared, and only 4 of them were chosen after considering the criteria for exclusion and inclusion. The articles under consideration were published between 2022 and 2023. In general, this review is beneficial for practitioners because it allows them to learn which journal articles are prepared to be used in determining the gaps of Students` Attitude on artificial intelligence. This study found that the students who have a positive attitude in using artificial intelligence can improved their English skills.